2006
DOI: 10.1159/000092993
|View full text |Cite
|
Sign up to set email alerts
|

Closed and Open Grade I and II Tibial Shaft Fractures Treated by Reamed Intramedullary Nailing

Abstract: Objective: To evaluate the results of closed and open grade I and II tibial shaft fractures treated by reamed nail and unreamed nailing. Subjects and Methods: Between 1997 and 2000, 119 patients with tibial shaft fractures were treated with reamed tibial nails. Postoperatively 96 patients (70 closed and 26 grade I and II open fractures) were followed clinically and radiologically for up to 18 months. The nail was inserted either by patellar tendon splitting or by nonsplitting technique. The nail was inserted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 48 publications
3
19
0
Order By: Relevance
“…The transpatellar approach causes anterior knee pain more frequently. 12,24,25 However, these findings have been disputed. 9,26 Meta-analysis was inconclusive in this area.…”
Section: Discussionmentioning
confidence: 99%
“…The transpatellar approach causes anterior knee pain more frequently. 12,24,25 However, these findings have been disputed. 9,26 Meta-analysis was inconclusive in this area.…”
Section: Discussionmentioning
confidence: 99%
“…Out of the 10 studies on intramedullary nailing as definitive management, only Tielinen et al [18] showed 0%. The other studies on intramedullary nailing presented less than 11% [4, 6, 10, 11, 16,17,19,[20][21][22], except for Sakaki et al [17], Park et al [4], and Kaftandziev et al [11] in which that rate was 17.85%, 22.0%, and 33.3%, respectively. Park et al [4] did not specify the percentages of superficial and deep infection.…”
Section: Infection Ratementioning
confidence: 98%
“…Besides, 10% of the fractures had delayed healing (over 6 months, according the paper), and they had to be dynamized and/or subjected to other procedures (reaming of the shaft, bone graft). In the other studies on IM Nailing as definitive management [2,6,10,11,16,17,19,[20][21][22][23][24] the nonunion rate was between 0% [6] and 11.1% [11].…”
Section: Nonunionmentioning
confidence: 99%
“…In fact, it is well-known that the mechanical conditions during the early phase of bone healing modify the course of healing and the quality and quantity of callus formation. 46,47 Moreover, the differences observed in shear interfragmentary strains may also delay the fracture healing process. 48 This is especially relevant in distal and mid-diaphyseal fractures stabilized by an unreamed intramedullary nail, where differences up to 50% were found.…”
Section: Daysmentioning
confidence: 99%